Решить уравнение: (X-3)^2+(x+4)^2-(x-5)^2=17x+24

0 голосов
50 просмотров

Решить уравнение:
(X-3)^2+(x+4)^2-(x-5)^2=17x+24


Алгебра (229 баллов) | 50 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

X^2 -6x+9+x^2+8x+16 -x^2+10x-25-17x-24 =0
x^2 -5x -24 =0
D = 25 -4(-24) =Y121;  D=11
x1= (5+11)/2 =8
x2 =(5-11)/2 = -3

(550k баллов)
0

^2 -6x+9+x^2+8x+16 -x^2+10x-25-17x-24 =0
x^2 -5x -24 =0
D = 25 -4(-24) =Y121; D=11
x1= (5+11)/2 =8
x2 =(5-11)/2 = -3

0 голосов
(x-3)^2+(x+4)^2-(x-5)^2=17x+24
\\\
x^2-6x+9+x^2+8x+16-x^2+10x-25-17x-24=0
\\\
x^2-5x-24=0
\\\
D=25+4\cdot24=121
\\\
x_1= \frac{5+11}{2}=8
\\\
 x_1= \frac{5-11}{2}=-3
Ответ: 8 и -3
(271k баллов)